Keeping U.S. Intelligence Effective : the Need for a Revolution in Intelligence Affairs. - Lahneman, William J. (Rowman & Littlefield Pub. Group, 2011)
Keeping U.S. Intelligence Effective: The Need for a Revolution in Intelligence Affairs explores whether the U.S. intelligence enterprise will be able to remain effective in today's security environment. Based on the demands currently being placed upon the intelligence community, the analysis concludes that the effectiveness of U.S. intelligence will decline unless it embarks upon an aggressive, transformational course of action to reform various aspects of its operations. In keeping with the emerging literature on this subject, the book asserts that a so-called Revolution in Intelligence Affa.